Cost Analysis Of Diarrhoea Treatment In The Infectious Diseases Hospital In Pune City - Gokhale R M; Pratinidhi A K; Garad S C (Wolters Kluwer Medknow Publications, 1999)
Research Question: What is the cost of diarrhoea treatment in the infectious diseases Hospital in Pune City? Objectives: To determine the cost of diarrhoea treatment borne by the hospital & the cost borne by the patients. Study design: Cross sectional study. Participants: Patients admitted to infections diseases hospital for diarrhoea treatment Sample Size: 112 Patients admitted to infectious diseases hospital for diarrhoea treatment Study variables: Age, Sex, Place of residence treatment by private practitioners, duration of stay in the hospital. Out come variables: Cost borne by the hospital and cost borne by the patient. Results: The average cost borne by the hospital for treatment of an episode of diarrhoea was Rs.164.87. When average duration of stay was 2.01 days and the average cost borne by the patient was Rs.111.36. The total cost was Rs.276.23.